Plus ça Change, Plus C'est La Même Chose: The 2015 Israeli elections. (December 2015) - Hazan, Reuven Y.; Diskin, Abraham
Abstract: In many ways, the 2015 parliamentary elections in Israel followed patterns that have been evident ever since the establishment of the state. The campaign positions of the parties, the politicians, and the voters related predominantly to defense and foreign affairs, and less to socio-economic policies. Religion-state issues in general, and the relationship between the Jewish majority and the Arab minority in particular, were also prominent. All these issues played a role in the 20th general elections held on 17 March 2015, just as they did in the first general elections in 1949.